(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The main objective of the study is to empirically evaluate the critical roles of small businesses in economic growth in India. A strong inverse relationship also exists between the incidences of small business economic growth. Thus, the empirical result establishes the linkage between small businesses, economic growth. Small businesses generate major economic activity in every industry sector, from construction and manufacturing to educational services and high technology. While their organizational structures vary widely, smaller companies often face similar challenges in a continually changing marketplace. These include finding and keeping skilled employees, controlling health care costs and other expenses, and meeting the competitive demands of an increasingly global economy.